2021
DOI: 10.3390/ijerph18063155
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining to Select Relevant Variables Influencing External and Internal Workload of Elite Blind 5-a-Side Soccer

Abstract: (1) Background: Data mining has turned essential when exploring a large amount of information in performance analysis in sports. This study aimed to select the most relevant variables influencing the external and internal load in top-elite 5-a-side soccer (Sa5) using a data mining model considering some contextual indicators as match result, body mass index (BMI), scoring rate and age. (2) Methods: A total of 50 top-elite visually impaired soccer players (age 30.86 ± 11.2 years, weight 77.64 ± 9.78 kg, height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 39 publications
2
17
0
1
Order By: Relevance
“…At all levels and kinds of soccer matches, the tactical role, individual playing position, the opponent, and the impulse of stimulus degree of motivation can affect the correlation between VO 2max and match running performance. It has been shown that some contextual variables can affect external load like match running distance [7]. However, Gamonales et al, (2020) [8] in a tournament for individuals with visual impairment showed similar match running distance (1,416 to 1,877 m).…”
Section: Relation Of Vo With Total Match Running Distance and Other P...mentioning
confidence: 99%
See 3 more Smart Citations
“…At all levels and kinds of soccer matches, the tactical role, individual playing position, the opponent, and the impulse of stimulus degree of motivation can affect the correlation between VO 2max and match running performance. It has been shown that some contextual variables can affect external load like match running distance [7]. However, Gamonales et al, (2020) [8] in a tournament for individuals with visual impairment showed similar match running distance (1,416 to 1,877 m).…”
Section: Relation Of Vo With Total Match Running Distance and Other P...mentioning
confidence: 99%
“…Generally speaking, the improvement of physiological variables can help people with disabilities to be healthier and more satis ed with their life [28]. Furthermore, the physical activity of people with visual impairment improves their social life because in most sports they socialize with other people, especially in team sports [7] which has a positive impact on their life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Es una adaptación del fútbol sala convencional, cuyo objetivo es facilitar algunas acciones específicas para personas con discapacidad visual (Gamonales, 2017;Gamonales, Muñoz-Jiménez, León & Ibáñez, 2018b). Además, los deportistas de Fa5 sufren un mayor número de impactos durante los entrenamientos y partidos que los jugadores de fútbol convencional (Gamonales, León, Rojas-Valverde, Sánchez-Ureña & Muñoz-Jiménez, 2021), como consecuencia de jugar de forma diferente y en ausencia de visión (Gamonales, Muñoz-Jiménez, León & Ibáñez, 2021).…”
unclassified